Good Corporate Governance Model in Indonesian Islamic Banking - Zulfikri Charis Darmawan; Sri Herianingrum (AFEBI Islamic Finance and Economic Review, 2020)
This study aims to examine the concept and implementation of Good Corporate Governance in Islamic banking in Indonesia. This research is a field research which is sharpened by the literature. This research is descriptive in nature, seeks to examine GCG policies and find ideas to strengthen regulations in compliance with sharia aspects and describes the implementation of GCG in Islamic banking in Indonesia. The method used in data analysis is a qualitative method, namely by presenting it in the form of descriptions and concepts. The performance of Islamic bank management, namely the implementation of GCG consisting of Transparency (Openness), Accountability, Responsibility, Professionalism, Independence, and Fairness, as well as being committed to Sharia Compliance, However, the author only focuses on Sharia Compliance. Then the assessment is carried out periodically and continuously and efforts are made so that it can be carried out properly in accordance with applicable regulations. This research focuses more on the concept and implementation of GCG in Islamic banking.Keywords: Good Corporate Governance (GCG), Sharia Bank Management Performance, Sharia Compliance.